Lignin Depolymerization and Conversion: A Review of Thermochemical Methods - Pandey, M. P.; Kim, C. S. (Chemical engineering & technology, 2011)
The structure of lignin suggests that it can be a valuable source of chemicals, particularly phenolics. However, lignin depolymerization with selective bond cleavage is the major challenge for converting it into value‐added chemicals. Pyrolysis (thermolysis), gasification, hydrogenolysis, chemical oxidation, and hydrolysis under supercritical conditions are the major thermochemical methods studied with regard to lignin depolymerization. Pyrolytic oil and syngases are the primary products obtained from pyrolysis and gasification. A significant amount of char is also produced during pyrolysis. Thermal treatment in a hydrogen environment seems very promising for converting lignin to liquid fuel and chemicals like phenols, while oxidation can produce phenolic aldehydes. Reaction severity, solvents, and catalysts are the factors of prime importance that control yield and composition of the product. An efficient and commercially competitive lignocellulosic biorefinery requires optimum utilization of all biomass components. Till date, lignin is the most underutilized component of a lignocellulosic biomass. However, lignin depolymerization with selective bond cleavage can convert it into various value‐added chemicals including monomeric phenols and phenolic aldehydes.